Cellular therapy for myocardial ischemia using a temperature-responsive biodegradable injectable polymer system with adipose-derived stem cells. Issue 1 (31st December 2021) - Yoshizaki, Yuta; Ii, Masaaki; Takai, Hiroki; Mayumi, Nozomi; Fujiwara, Soichiro; Kuzuya, Akinori; Ohya, Yuichi
ABSTRACT: Adipose-derived stem cell (AdSC) has been attracting attention as a convenient stem cell source. Not only AdSC can differentiate into various tissue cells, but it can also accelerate cell proliferation, anti-inflammation, and angiogenesis by secreting paracrine factors. Studies have demonstrated AdSC treatment of ischemic heart. However, an improvement in the remaining live AdSCs administered at the injected site while maintaining paracrine factor secretion is desired to achieve effective regenerative medicine. We previously reported the ABA-type tri-block copolymer of poly(ɛ-caprolactone- co -glycolic acid) and poly(ethylene glycol) (tri-PCG), exhibiting temperature-responsive sol-to-gel transition as biodegradable injectable polymer (IP) systems. Moreover, we recently reported that the biodegradable temperature-triggered chemically cross-linked gelation systems exhibited longer gel state durations using tri-PCG attaching acryloyl groups and a polythiol derivative. In this study, we explored this IP-mediated AdSC delivery system. We investigated the cell viability, mRNA expression, and cytokine secretion of AdSCs cultured in the physical or chemical IP hydrogels. Both of these IP hydrogels retained a certain number of viable cells, and RT-PCR and ELISA analyses revealed that mRNA expression and secretion of vascular endothelial growth factor of the AdSCs cultured in the chemical hydrogel were higher than the physical hydrogel. Moreover, AdSCs injected with the chemical hydrogel into ischemic heart model mice showed longer retention of the cells at the injected site and recovery from the ischemic condition. The results mean that the IP system is a promising candidate for a stem cell delivery system that exhibits the recovery of cardiac function for myocardial infarction treatment. Graphical Abstract: uf0001